Management Classroom Management Through Islamic Religious Education Learning at SMK Al Hurriyah Karawang - Fajar Firdaus; Oyoh Bariah; M. Makbul (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Education is very important in building the nation's generation by creating advanced human resources. With this progress, there is a teacher who has a very important role in providing strategic teaching and classroom management. This study aims to describe classroom management in Islamic religious education subjects and address classroom management problems at SMK Al Hurriyah Karawang. The research used a descriptive qualitative approach, the research subjects were addressed to Islamic religious education teachers and students. Data collection techniques in writing this using interview techniques, observation, and documentation. The results of this study indicate that there are several classroom management, namely, preparing rules in the classroom, making procedures for items in class, and preparing learning activities by preparing student attendance and assessment books. While the way to overcome classroom management problems is to show responsiveness, pay attention to all students, and reprimand if someone violates it.